Mortality and complications following total aortic arch replacement: 14 years’ experience - Vutthipong Sanphasitvong (2022)
Background: Open total arch replacement is one of the most challenging procedures in cardiothoracic surgery and is the gold standard treatment for aortic arch pathology. Total arch replacement is associated with high rates of mortality and neurological morbidity. Using 14 years of data, we studied postoperative, in-hospital mortality, major complications, and examined associated risk factors. Materials and method: Medical records of patients who underwent open, total arch replacement surgery at Siriraj Hospital from 2006 to December 2019 were reviewed. Demographic data, clinical factors, preoperative status, intraoperative data, and postoperative data were analyzed. Result: A total of 330 patients were included and 36 (10.9%) died in the hospital. More than one concomitant operation (odds ratio (OR) 5.16, p < 0.001) and emergency operation (OR 3.45, p = 0.003) were risk factors for in-hospital mortality. Major postoperative morbidity occurred in 124 (37.7%) patients (124 of 329). Emergency operation (OR 2.88, p <0.001), preoperative creatinine clearance < 60 ml/ min/ 1.73 m2 (OR 2.04, p = 0.004), and aortic cross-clamp time > 180 min (OR 1.75, p = 0.022) were risk factors for major postsurgical complications. Conclusion: In-hospital mortality after total arch replacement was 10.9% compared to international reports. Emergency operation was a major risk factor for both mortality and major complications. More than one concomitant operation, especially coronary artery bypass graft, more than doubled the risk of major complications.